Viabilidade econômica da produção de crisântemos em vaso no município de Atibaia-SP - Shiroto, Caio Shigueaki [UNESP]; Peres, Narah Vieira [UNESP]; Sabbag, Omar Jorge [UNESP] (My University, 2016)
The segment of flower production in Brazil has shown remarkable development in recent years. The chrysanthemum is a product of extensive sales throughout Brazil and the diversity of types and colors, resistance to transport, excellent durability, and its easy adaptation to different regions make it as one of the main products in the various markets. This study aimed to evaluate the cost and economic viability of commercial production of potted chrysanthemums in the Atibaia, Sao Paulo State. For the total cost of production (6,413 vases/month) expenses cuttings accounted for 36.4% of inputs and 26.4% of the EOC (effective operational cost), followed by labor, with 16% of the TOC (total operational cost) achieving a profitability index 27.7%. It was found, based on cash flow, an IRR (internal rate of return) of 10.27% IRR (internal rate of return) already for the 6th productive year, showing attractive results for this segment considering the improving producer profitability is proportional to better production indicators. Note that to get a higher return activity, more efficient managements are required, resulting in lower losses and higher operating earnings, being necessary to take into account the cost management and production system are also essential to success in cultivation.
Economic viability of potted chrysanthemums production in Atibaia, Sao Paulo state
Keywords: Costs; Dendranthema x grandiflorum; Investment analysis; Profitability